Fractal aggregation and disaggregation of newly formed iron(iii) (hydr)oxide nanoparticles in the presence of natural organic matter and arsenic. Issue 3 (4th May 2016) - Neil, Chelsea W.; Ray, Jessica R.; Lee, Byeongdu; Jun, Young-Shin
Abstract : This study provides for the first time in situ observations of organic matter and arsenic effects on iron(iii ) (hydr)oxide precipitation. Abstract : Water chemistry affects the nucleation kinetics, precipitate morphology, and quantity of iron(iii ) (hydr)oxide nanoparticles, directly impacting the reactive surface area of geomedia and fate of associated waterborne contaminants. In this study, we utilized in situ grazing-incidence small angle X-ray scattering (GISAXS) and complementary ex situ techniques to investigate heterogeneous iron(iii ) (hydr)oxide nucleation on quartz in the presence of natural organic matter (NOM) and arsenate. Results indicate unique fractal aggregation behavior in the systems containing NOM and precipitating iron(iii ) (hydr)oxide nanoparticles. Furthermore, the coexistence of arsenic and NOM lead to the formation of two distinct particle size ranges: larger particles dominated by arsenic effects, and smaller particles dominated by NOM effects. These new findings provide important implications for understanding the nucleation, growth, and aggregation of iron(iii ) (hydr)oxides in aqueous systems where NOM is present, such as natural surface waters and water and wastewater treatment plants. This study also offers new insight into how NOM-associated iron(iii ) (hydr)oxides can interact with aqueous contaminants such as arsenate.